Prevalence of alcohol consumption and related factors among students of higher education centers in one of the northeastern cities of Iran - Behrad Pourmohammadi; Moahammad Ali Jalilvand (AIMS Press, 2019)
Introduction: Knowing the prevalence and the factors associated with alcohol abuse among students can be an important step in initiating preventive measures. The purpose of this study was to determine the prevalence of alcohol consumption and its related factors in students of higher education centers in one of the northeastern cities of Iran in 2017. Methods: This descriptive-analytical study was performed on 668 students from 7 higher education centers. The samples were selected by stratified random sampling. The valid researcher-made questionnaires were issued to the subjects, and were collected immediately after being filled out. The obtained data were analyzed using appropriate statistical tests. Results: Ninety-two (13.77%) students had history of alcohol consumption, with 55.6% continued to drink alcohol. The mean age of the consumers was 23.92 years, of whom 77.41% were male, 75% were single, 55.43% were non-indigenous, and 74.46% had history of smoking. 81.52% of the subjects were undergraduates, while 36.95% studied mathematics and engineering. There was a significant relationship between alcohol consumption and age, gender, GPA, being non-indigenous, personal residence, smoking, history of alcohol consumption in family and friends, satisfaction with academic major and city in which they study (p < 0.05). Conclusion: The findings showed that alcohol consumption was relatively high in students of higher education centers and many variables (ten out of fifteen studied variables) were involved in this process. Therefore, careful planning and serious measures are needed to prevent this problem.